The Country and the City in the Cuban Revolution - Michelle Chase (Universidad de Los Andes, 2011)
This article examines the interplay between city and country in the earliest years of the Cuban Revolution of 1959. It argues that the mass movement of Cubans, especially youths, between urban and rural areas was a major factor in contributing to the radical consciousness of the 1960s. At the same time, these early initiatives also contributed to the growing disaffection with the Cuban revolution. The article, thus, lends insight into the excitement and polarization of Cuba's "revolutionary moment."